Novel design of tool for joining hollow extrusion by friction stir welding. (1st April 2013) - Huang, Y X; Wan, L; Lv, S X; Feng, J C
<x xml:space="preserve">Abstract</x> In the present work, we design a novel tool called self-support FSW (SSFSW) with adjustable dip angle to join the aluminium hollow extrusion. This tool consists of a big concave upper shoulder and a small convex lower shoulder. Compared with conventional FSW, it eliminates root flaws and does not need backing bars during operation. In particular, the SSFSW can adapt to variation of thickness and does not need predrilled pilot holes, resulting in simplifying the welding process compared with the bobbin tool FSW tool. Significant changes are observed at the cross-section of the SSFSW joint, which looks like a 'waist'. The average tensile strength and elongation of 6005A aluminium alloy joint with a thickness of 5 mm is 190 MPa and 6·86% respectively. Furthermore, the failure of specimen presents a ductile fracture in the typical joint.